Invasiveness risk of biofuel crops using Jatropha curcas L. as a model species. (22nd May 2013) - Negussie, Aklilu; Achten, Wouter M. J.; Norgrove, Lindsey; Hermy, Martin; Muys, Bart
Abstract: Biofuel crops are promoted as a climate friendly alternative to fossil energy. Yet environmental risks such as potential biodiversity loss are not always adequately considered. This might occur directly as a consequence of land‐use change from natural systems to biofuel plantations, but also through invasive behavior of the biofuel species, as it might disperse and establish into adjacent natural systems. Therefore, there is a need to perform ex‐ante invasiveness risk assessments including field trials on new biofuel species before they get promoted and expanded on a large scale. This perspective uses Jatropha curcas L. as a model biofuel crop and reviews the biological traits and the circumstantial factors which may contribute to its invasive behavior. J. curcas has recently received much attention as a biodiesel 'wonder crop' and is being planted at large scale without scientific study on its invasiveness risk. We applied two risk assessment frameworks to provide an ex‐ante invasiveness risk assessment and obtained that J. curcas is a species with a high invasiveness risk, which is in contradiction with recent experimental evidence. We discuss the limitations of the available risk assessment frameworks, which may have led to unreliable prediction. We interpret the outcome of this theoretical exercise with some recommendations for the selection, introduction, cultivation, and processing stages of J. curcas and other biofuel crops to minimize invasiveness risk. Finally we point to the responsibilities of investors and governments and the need for integrated research of the whole biofuel production supply chain to avoid bio‐invasions. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd